METODE DI PENDIDIKAN ANAK USIA DINI - Ermiana, Ida (MAJALAH ILMIAH PEMBELAJARAN, 2010)
Early childhood education is a form of essential education for human life in the future. Education related to all of life experiences in different environments which have positive influence for individual development for lifetime. There are two reasons why parents bring their children to the school; the first one is so that their children have many friends to get playing or to learn how to socialize and the second one is to prepare their children for school. Parents want their children learn in early, learn to socialize, practice their maturity, and even build their responsibility in order to be ready to go to school. The selection method for the early childhood education (PAUD) needs to consider in some factors which do not reduce other potentials, for example by using method which involves children actively, considers to children interest and need, comprehends to children character, and knowswell the stages of children development. The method for the childhood is also adjusted with the stage of children development in which they play while studying. As a teacher or parents, we don't need to force our children to study something. The applied method should also give opportunity for them to explore their world. In exploring, children tend to be acquainted with the religion, art, morality, politeness, and also beauty.